A proposal for a new reading itinerary concerning the works of Aurelius Prudentius - Santos Monteiro Oliveira, Rodrigo (Romanitas - Revista de Estudos Grecolatinos, 2021)
Book review of: Resenha de: GONÇALVES, A. T. M. A arte poética a serviço do proselitismo cristão: relendo os poemas de Aurélio Prudêncio Clemente (séculos IV/V). Jundiaí: Paco, 2020. 276 p.
Keywords: Late Antiquity; Christian literature; Prudentius